PENGARUH KETERAMPILAN KERJA, LINGKUNGAN KERJA FISIK DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT INDOMARCO PRISMATAMA WILAYAH DENPASAR SELATAN - I Putu Dedy Pratama; Anak Agung Dwi Widyani; I Dewa Made Arik Permana Putra (VALUES, 2024)
Human resource management has a crucial role in achieving organizational performance and is closely related to employee performance. The research at PT Indomarco Primatama South Denpasar Branch aims to assess the influence of work skills, physical work environment and workload on employee performance. Data collection was carried out by distributing questionnaires to 70 employees using accidental sampling technique. Based on the results of multiple linear regression analysis, it shows that work skills, physical work environment and workload have a positive and significant effect on performance. Therefore, it is necessary to increase skills through training, attention to the physical work environment, and adjustment of incentives according to realistic targets according to employee abilities.